(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In the rural areas of Assam, the leaves of Calamus floribundus are in use among the traditional healers for the treatment of different skin related problems. Assessment of in vivo wound healing activity of the plant was undertaken to unearth the extent of its healing potential. Methanolic extracts of the leaves of C. floribundus was applied topically on the mice having excision wounds. For the wound healing potential assessment, different parameters such as rate of wound contraction, epithelialization period, tensile strength, content of DNA, protein, hydroxyproline, expression level of the growth factor and pro-inflammatory cytokines, histopathological and ultrastructural evaluations were carried out. The results indicated that the application of the extract lead to the significant increase in the rate of wound contraction, tensile strength; DNA, protein and hydroxyproline content. The expression of PDGF-AA was upregulated and the cytokines levels were downregulated in the extract treated group and all the values were found to be comparable to that of the reference drug treated group. The results were further supported by morphometric, histological and ultrastructural observations. The findings of our in vivo study indicate that the methanolic crude extracts of the leaves of C. floribundus has positive effect on the healing of excision wounds in Swiss albino mice.